1997
DOI: 10.1152/jappl.1997.83.5.1461
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, alveolar macrophage function, and susceptibility to respiratory infection

Abstract: The effects of exercise on susceptibility to respiratory infection were determined by using a murine model of intranasal challenge with herpes simplex type 1 virus (HSV-1). Two doses of treadmill exercise were assessed: moderate short-term (30 min) exercise and prolonged strenuous exercise to voluntary fatigue (2.5-3.5 h). Morbidity and mortality among exercised and control mice were compared after intranasal challenge with HSV-1. We also assessed the ability of alveolar macrophages to restrict HSV-1 viral rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
107
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 29 publications
9
107
0
Order By: Relevance
“…Data generally support the hypothesis that exercise stress can lead to immunosuppression and increased risk of infection [morbidity (time to sickness), symptom severity, and mortality (time to death)] (3,4,10,12,27,30). The mechanisms for the increased susceptibility to infection following intense exercise are thought to be mediated by alterations in the stress response.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Data generally support the hypothesis that exercise stress can lead to immunosuppression and increased risk of infection [morbidity (time to sickness), symptom severity, and mortality (time to death)] (3,4,10,12,27,30). The mechanisms for the increased susceptibility to infection following intense exercise are thought to be mediated by alterations in the stress response.…”
mentioning
confidence: 75%
“…Studies have focused on alterations in macrophage function as a mechanism for the detrimental effects of exercise on susceptibility to viral infection (10,12). Macrophages act as a first line of defense in eliminating viral pathogens by inhibiting virus growth within itself, as well as to inactivate extracellular virus, suppress virus replication in adjacent cells, and destroy infected cells (46).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, exhaustive exercise decreases alveolar macrophage antiviral function, an effect that is correlated to increased susceptibility to herpes simplex virus 1 infection. [43][44][45] A follow-up experiment designed to determine the role of stress hormones in this response suggested that the reduction in alveolar macrophage antiviral resistance was likely related to increased release of adrenal catecholamines, but not corticosterone. 43 These data demonstrate that the effects of exercise on macrophage function depend on the function measured and the dose of exercise used.…”
Section: Monocyte/macrophage Functionmentioning
confidence: 99%